Rethinking liquidity: A critical macro-finance view - Fabian Pape (Finance and Society, 2020)
This forum contribution critically rethinks the macro-financial approach to liquidity by focusing more explicitly on its public-private hybrid dimension. To do so, it introduces the notion of a "liquidity regime": a heuristic device aimed at tracking the ensemble of social relations and institutions that govern the coherence of the payments system at any given time. A key insight that emerges from this approach is that the ability to make markets and access liquidity is never neutral or apolitical. What requires closer attention, therefore, is precisely how the interaction between public authorities and private market participants affords some actors greater leverage in shaping the financial system.
Keywords: 300